Beyond Term Indexing: A P2P Framework for Web Information Retrieval - Podnar, I.; Rajman, M.; Luu, T.; Klemm, F.; Aberer, K. (Informatica)
Beyond Term Indexing: A P2P Framework for Web Information Retrieval